E-LEARNING ENVIRONMENT AT INNOVATIVE UNIVERSITY - Gennady A. Vorobiev (Высшее образование в России, 2022)
The article focuses on the main elements of PSLU e-environment, describes the activities of the Research and education center for IT-culture and innovations in informatization of Pyatigorsk State Linguistic University.